Misconceptions and Critical Thinking Ability In Undergraduate Exercise Science Students, Vocational Fitness Students, and Exercise Professionals - Jolley, Daniel (Curtin University, 2019)
This research is the first known cross-sectional and longitudinal investigation of misconceptions and critical thinking in exercise science and fitness students and professionals. Misconceptions were higher in students than degree-qualified professionals, though there was no difference between vocational graduates and vocationally-qualified personal trainers. An online, content-specific critical thinking course was effective in reducing misconceptions and improving critical thinking ability in professionals. Critical thinking appears to be more important than specific knowledge in reducing misconceptions.